1989
DOI: 10.1182/blood.v73.5.1340.bloodjournal7351340
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution following bone marrow transplantation: comparison of recipients of T-cell depleted marrow with recipients of conventional marrow grafts

Abstract: The reconstitution of hematopoietic cells and in vitro assays of immunologic function have been followed in leukemic patients after conventional bone marrow transplantation (BMT) (N = 34) and T-cell depleted BMT (N = 52) from human leukocyte antigen (HLA)-identical sibling donors. No effects of the T-cell depletion could be seen on the recovery of myeloid or lymphoid cells as measured by the day to engraftment or by the absolute number of cells through day 100. Normal numbers of lytically active natural killer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 0 publications
5
32
1
Order By: Relevance
“…Very early after transplant, all lymphocyte subsets measured were higher in NST patients; however, by 6 weeks, equivalent numbers of most T-cell subsets were achieved in TCD recipients despite a four log difference in the number of T cells infused at transplant. Our results are similar to those reported by Keever et al (1989), in which there were no quantitative differences in absolute counts of T cells between patients receiving T-cell-depleted and unmanipulated BMT, and Morecki et al (2001), who reported similar levels of lymphocyte subsets in myeloablative and low-intensity conditioning transplants.…”
Section: Discussionsupporting
confidence: 91%
“…Very early after transplant, all lymphocyte subsets measured were higher in NST patients; however, by 6 weeks, equivalent numbers of most T-cell subsets were achieved in TCD recipients despite a four log difference in the number of T cells infused at transplant. Our results are similar to those reported by Keever et al (1989), in which there were no quantitative differences in absolute counts of T cells between patients receiving T-cell-depleted and unmanipulated BMT, and Morecki et al (2001), who reported similar levels of lymphocyte subsets in myeloablative and low-intensity conditioning transplants.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, titres of isoagglutinins against ABO antigens absent both on recipient and donor RBCs decreased during the early post-transplant period, then rose subsequently at a median of 59 d posttransplant in most cases. This phenomenon of a posttransplant increase in isoagglutinin titres might reflect antibody production by donor-derived B-lymphocytes, and is consistent with other studies that showed reconstitution of B-lymphocyte number and function within 1-2 months after allogeneic stem cell transplantation (Noel et al, 1978;Ault et al, 1985;Keever et al, 1989). Unrelated stem cell transplantation and use of cyclosporine plus methotrexate for GVHD prophylaxis tended to be associated with delayed immunohaematological reconstitution compared with sibling transplantation and use of cyclosporine only respectively.…”
Section: Upnsupporting
confidence: 89%
“…Ottinger et al (1996) observed a normalization of the B-cell count as late as 11 months post alloHCT in adults treated with GvHD prophylaxis of CsA and MTX. However, Keever et al (1989) reported an earlier time period of 6 months post alloBMT to normalization of B-cell count. In our group, the B-cell count returned to normal at 4-6 months after alloHCT.…”
Section: Discussionmentioning
confidence: 99%